Service Quality dan Implikasinya Terhadap Kepuasan Pelanggan - Resti Siti Nur Cahyati Hidayat; Maya Setiawardani (Jurnal Riset Bisnis dan Investasi, 2017)
The high level of society mobility needs to be supported by adequate infrastructures. Sufficient and adequate toll road infrastructure is able to increase the acceleration of a country's economic and social development through the creation of effectiveness and resulting efficiency. Optimal service delivery can gain customer satisfaction. One approach to measure service quality that many used as a reference is SERVQUAL (Service Quality). There are five dimension on servqual model, that is reliability, assurance, tangible, emphaty and responsiveness. The purpose of this study is to determine the level of customer satisfaction in order to improve the quality of service and to know the service attributes that are prioritized to be maintained and improved by PT Jasa Marga (Persero) Branch Purbaleunyi. Data processing methods in this study using the validity, reliability, classical assumption test, and descriptive statistical analysis. While the data analysis methods used are simple linear regression analysis, correlation, coefficient of determination and quadrant analysis. The results of this study indicate that service quality variables have positive and significant impact on customer satisfaction at Purbaleunyi toll road.